Administrasi Personalia Pendidikan - Agustina, Natasya (STAI Tebing Tinggi Deli, 2024)
Education is a forum in which business activities in growing will develop the basic potential of humans and groups, by gaining knowledge for good results and achievements, education creates a perspective which must be developed effectively. Administration in institutions or agencies has often been heard saying, administration is a factor that can be interpreted as very important in the conditions of the rules for every activity for the progress of an agency. Qualitative research is basically research based on literature study. This qualitative research by searching library studies collects journals, documents and theses related to the Personnel Administration of Educational Institutions which are based on the writing of this article, then linked to this research. This research describes the results of presentations from journals, books and other references, to find out the relationship between the Administration implementation process Personnel in the educational institution.